Challenges Facing Black Owned Small and Medium Construction Companies: A Case Study of Nelspruit – Mbombela Municipality, South Africa - C.O., Aigbavboa (Journal of Economics and Behavioral Studies, 2014)
The purpose of the paper is to investigate current challenges and problems facing small and medium size contractors (SME) in Mbombela (Nelspruit) - Mpumalanga Province of South Africa. This study was necessitated because the importance of small and medium sized enterprises in national building and economic development is of paramount importance in the South Africa economic debate. The primary data for the study was collected through a structured questionnaire survey which was distributed to Small and medium contractors within grade 1-4 of the South Africa Construction Industry Development Board. The survey results indicated that external factors such as high competition when tendering for construction jobs within the CIDB category is a major challenge the SME’s face’s in the procurement of work. Also, internal factors such as poor administrative management within the company, lack of skilled professionals and lack of capacity to deliver on certain project were the greatest challenges faced by the construction companies. The scope of this study is only focused on small and medium size contractors in Nelspruit (Mpumalanga province). In addition, the study is not focused on large established contractors in South Africa. The South African construction industry will continue to provide jobs but intervention is needed to develop the SME’s contractors who contribute a greatly to the economy.